2017
DOI: 10.1111/gfs.12313
|View full text |Cite
|
Sign up to set email alerts
|

Harvest management based on leaf stage of a tetraploid vs. a diploid cultivar of annual ryegrass

Abstract: Leaf stage-dependent defoliation is linked to the plant's physiological status and may be a more suitable criterion than time-based intervals for harvesting forage grasses, but no reports of research with annual ryegrass (Lolium multiflorum Lam.var. westerwoldicum) were found. To address this, a 2-year field study was carried out at Raymond, MS, on a Loring silt loam soil (fine-silty, mixed, thermic Typic Fragiudalfs). Forage production, morphological characteristics and nutritive value responses to defoliatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 70 publications
1
16
0
Order By: Relevance
“…Before vernalisation between February and May 2018, all chicory treatments accumulated on average 6.4 ± 0.98 kg/ha DM herbage per GDD. Variation in accumulated herbage mass in response to contrasting regrowth intervals of the same forage species likely result from differences in plant density and plant size [28,51]. In the current experiment, no significant differences in plant density between treatments were found (Table 5).…”
Section: Before Vernalisationmentioning
confidence: 53%
See 3 more Smart Citations
“…Before vernalisation between February and May 2018, all chicory treatments accumulated on average 6.4 ± 0.98 kg/ha DM herbage per GDD. Variation in accumulated herbage mass in response to contrasting regrowth intervals of the same forage species likely result from differences in plant density and plant size [28,51]. In the current experiment, no significant differences in plant density between treatments were found (Table 5).…”
Section: Before Vernalisationmentioning
confidence: 53%
“…Our results showed that both the size of the roots and their concentration of WSC were lower for the 300 GDD plants than the 600 GDD plants before and after vernalisation. Similarly, Donaghy and Fulkerson [57] and Solomon et al [51] have reported a decline in root WSC concentration from longer to shorter defoliation intervals in perennial and annual ryegrass plants, respectively.…”
Section: Root Size and Concentration Of Stored Carbohydratesmentioning
confidence: 82%
See 2 more Smart Citations
“…However, due to difficulty of measuring aspects of light interception and LAI in field conditions, the challenge for scientists in grassland ecophysiology is to translate the ecophysiological principles into sward characteristics that should be as efficient as LAI and ease to apply, so farmers could monitor the grazing process and make the "complex seem simple" (Chapman, 2016). In this context, several grazing management guidelines have been developed, with the definition of sward height targets (Carvalho et al, 2016;Hodgson, 1990) and leaf stage indicator (Fulkerson and Slack, 1995;Gomide and Gomide, 1999;Solomon et al, 2017) being some of the most used. Independently of the sward structural characteristics used, the idea is to maintain the optimum balance between leaf growth and senescence favoring high herbage accumulation and utilization efficiency, ensuring pasture persistence and herbage consumption by animals.…”
Section: General Principles Of Grazing Managementmentioning
confidence: 99%